A comparison of isotope ratio mass spectrometry and cavity ring-down spectroscopy techniques for isotope analysis of fluid inclusion water - Graaf, Stefan de; Vonhof, Hubert B.; Weißbach, Therese; Wassenburg, Jasper A.; Levy, Elan J.; Kluge, Tobias; Haug, Gerald H. (Rapid communications in mass spectrometry, 2020)
Rationale Online oxygen (δ18O) and hydrogen (δ2H) isotope analysis of fluid inclusion water entrapped in minerals is widely applied in paleo-fluid studies. In the state of the art of fluid inclusion isotope research, however, there is a scarcity of reported inter-technique comparisons to account for possible analytical offsets. Along with improving analytical precisions and sample size limitations, interlaboratory comparisons can lead to a more robust application of fluid inclusion isotope records. Methods Mineral samples—including speleothem, travertine, and vein material—were analyzed on two newly setup systems for fluid inclusion isotope analysis to provide an inter-platform comparison. One setup uses a crusher unit connected online to a continuous-flow pyrolysis furnace and an isotope ratio mass spectrometry (IRMS) instrument. In the other setup, a crusher unit is lined up with a cavity ring-down spectroscopy (CRDS) system, and water samples are analyzed on a continuous standard water background to achieve precisions on water injections better than 0.1‰ for δ18O values and 0.4‰ for δ2H values for amounts down to 0.2 μL. Results Fluid inclusion isotope analyses on the IRMS setup have an average 1σ reproducibility of 0.4‰ and 2.0‰ for δ18O and δ2H values, respectively. The CRDS setup has a better 1σ reproducibility (0.3‰ for δ18O values and 1.1‰ for δ2H values) and also a more rapid sample throughput (<30 min per sample). Fluid inclusion isotope analyses are reproducible at these uncertainties for water amounts down to 0.1 μL on both setups. Fluid inclusion isotope data show no systematic offsets between the setups. Conclusions The close match in fluid inclusion isotope results between the two setups demonstrates the high accuracy of the presented continuous-flow techniques for fluid inclusion isotope analysis. Ideally, experiments such as the one presented in this study will lead to further interlaboratory comparison efforts and the selection of suitable reference materials for fluid inclusion isotopes studies.
Gesehen am 02.10.2020